Eastern partnership migrants in Germany: Outcomes, potentials and challenges - Costanza Biavaschi; Klaus F. Zimmermann (IZA Journal of European Labor Studies, 2014)
Despite the ongoing dialogue on facilitating mobility between the European Union and the Eastern Partnership (EaP) countries, very little is known about the magnitude and characteristics of migration from these countries. We find that EaP migrants experience worse labor market outcomes than other migrant groups, but current and potential migrants hold qualifications in those areas were skill shortages are expected. Therefore, the monitoring and supervision of EaP integration will be consequential in order to understand how much of the current brain waste is driven by poor assessment of foreign qualifications, and to unleash the potential of migration for the German economy.
Keywords: J15; J24; J61; J62; 330; Labor mobility; Eastern Partnership countries; Brain waste; Foreign qualifications